Counting Missing Women - A Reconciliation of the 'Flow Measure' and the 'Stock Measure' - Cara Ebert; Stephan Klasen; Sebastian Vollmer (Institute for Replication (I4R), 2022)
'Stock estimates' of missing women suggest that the problem is concentrated in South and East Asia and among young children. In contrast, 'flow estimates' suggest that gender bias in mortality is much larger, is as severe among adults as it is among children in India and China, and is larger in Sub-Saharan Africa than in India and China. We show that the different stock and flow measure results rely on the choice of the reference standard for mortality and an incomplete correction for different disease environments in the flow measure. Alternative reference standards reconcile the results of the two measures.
Keywords: J16; D63; I10; 330; Missing women; gender bias; mortality; disease; age; Sub-Saharan Africa; China; India